Why do lower courts refer in the absence of a legal obligation? Irish eagerness and Dutch disinclination. Issue 6 (December 2019) - Krommendijk, Jasper
The majority of requests for a preliminary ruling from the EU Court of Justice comes from lower national courts. This is surprising because such courts are, contrary to the highest national courts, not obliged to refer on the basis of Article 267 TFEU. This article examines why Dutch and Irish lower courts have decided to refer or not in the absence of such a legal obligation. It does so on the basis of an analysis of court decisions complemented with 45 interviews with judges and legal secretaries. The article shows that there is a wide variety of reasons (not) to refer, including pragmatic and practical considerations. Politico-strategic reasons play a smaller role than one would expect on the basis of the literature to date. The most important factor affecting the courts' willingness to refer is the way in which lower court judges see their role in relation to the highest court(s). This factor also explains the difference between Ireland and the Netherlands. While most Irish references are made by lower courts, around two thirds of the references in the Netherlands stem from the highest courts. Most Irish judges adopted a 'better sooner than later' logic, while the majority of Dutch judges emphasized that the highest courts have more time and expertise.